Distribution of the Synthetic Cathinone α-Pyrrolidinohexiophenone in Biological Specimens. Issue 1 (27th July 2018) - Vignali, Claudia; Moretti, Matteo; Groppi, Angelo; Osculati, Antonio Marco Maria; Tajana, Luca; Morini, Luca
Abstract: We report the analysis of the synthetic cathinones α-pyrrolidinohexiophenone (α-PHP) and α-pyrrolidinopentiophenone (α-PVP), both pyrovalerone derivatives, in blood, urine, gastric contents, main tissues and hair of a deceased person. Qualitative and quantitative analyses were performed by LC–MS-MS. All the biological samples were collected during autopsy and extracted/purified onto a solid phase extraction cartridge before instrumental analysis. The method was validated for blood and urine and proved to be highly sensitive and specific for both the synthetic cathinones (limit of detection: 0.2 ng/mL and limit of quantification: 0.5 ng/mL). Analyses provided negative results for α-PVP in all biological samples except for the 2-cm proximal hair segment, confirming that the young man had consumed in the last 2 months this compound; instead hair analysis proved that the man was a heavy α-PHP user. α-PHP was identified and quantified in biological fluids and tissues. Interestingly, bile and urine concentrations (1.2 and 5.6 ng/mL, respectively) were fairly lower than blood collected into the thoracic cavity (15.3 ng/mL). The highest concentrations were measured for lung (71.1 ng/mL) and spleen (83.8 ng/mL). Concentrations of 3.5, 7.9, 4.7 and 23.6 ng/mL were measured in liver, kidney, brain and heart, respectively. Even if it is not possible to evaluate the presence of this drug in biological samples as a cause of death, to our knowledge, this is the first case of α-PHP finding in postmortem samples, and its potential toxic effects should be elucidated in the future.